The Decomposition of Global Conformal Invariants: Some Technical Proofs. I - Alexakis, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
This paper forms part of a larger work where we prove a conjecture of Deser and Schwimmer regarding the algebraic structure of ''global conformal invariants''; these are defined to be conformally invariant integrals of geometric scalars. The conjecture asserts that the integrand of any such integral can be expressed as a linear combination of a local conformal invariant, a divergence and of the Chern-Gauss-Bonnet integrand.